Identification and Distribution of Cutinase - Ling Qia Su (Cutinase: Preparation and Application, 2021)
Cutinases are present in bacteria and fungi, which exhibit a hydrolytic capacity for the ester bonds in cutin. Currently, cutinases from fungi were extensively investigated. So far, there are few studies on cutinases from bacteria because of the lack of open reading frames. In this study, cutinase was secreted from Thermobifida fusca that induced by cutin, which was purified with the p-nitrophenyl butyrate hydrolyzing activity. Mass fingerprinting analysis showed that the protein band matched two proteins, Tfu_0883, and Tfu_0882, which have 93% similarity with both sequences. Then, these genes were cloned and overexpressed in Escherichia coli, which were identified as cutinases by their capability to hydrolyze cutin. This is the first report of cutinase encoding genes from bacterial source. Also, the bacterial and fungal enzymes are demonstrated no sequence similarity, which was classified into prokaryotic and eukaryotic cutinase subfamilies, respectively.